Jabatan Notaris Dalam Era Perkembangan Teknologi Informasi Dan Komunikasi - Memah, Genesia Hardina (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 5 No 1 (2020), 2020)
The purpose of this research is to find the influences of the development on technology information and communication on the administrative and the material (substantive) aspect to a notary, wherein this research normative legal methodology is conducted with the results as follow there is a positive administrative influence of technology information and communication such as the use of e-government in the communication of notary or candidate of a notary with government and the increased office effectiveness. However, there is also a negative influence such as the ease of publication and self-promotion; thus, the Indonesia Notary Association need to always give direction through a regular meeting. The impact of technology information and communication on the administrative aspect is that it could result on clash between the Law of Notary with other law that already regulate the utilization of technology information and communication where from the theory point of view, the concept of lex specialis derogat legi generali can be used while from the practical perspective, it is preferable to have memorandum of understanding between the Indonesian Notary Association with the Indonesian Nasional Police (Polri).